Integrating NIR and genomic data for predicting fiber and sucrose content in sugarcane - Gonçalves, Mateus Teles Vital (Universidade Federal de Viçosa, 2019)
The main goal of this dissertation was to investigate candidate methodologies to circumvent some of the bottlenecks of the sugarcane genetic breeding program of the Universidade Federal de Viçosa (PMGCA). In chapter one, we developed regression and classification models using near-infrared spectroscopy to predict and classify sugarcane clones based on two feedstock quality parameters. The values measured by reference methods and predicted by PLS and PLS-DA models were compared. The PLS models developed had moderate accuracies. The correlation coefficients of prediction obtained were: 0.732 for fibre content and 0.665 for sucrose content. The PLS-DA models built to classify clones based on PC% showed the ideal value of 1 for sensitivity, whereas models based on FIB% showed a moderate value of 0.758. Both models exhibited similar classification errors: 0.185 and 0.195 for FIB% and PC%, respectively. These results indicate the feasibility of NIR spectroscopy coupled with multivariate analysis for the substitution of current time-consuming methods in the evaluation of large populations of sugarcane clones. In chapter two, we investigate whether the accuracy of genomic selection is improved, by combining the NIR spectra matrix to a SNP genotyping matrix into a single regression analysis. The accuracy of genomic selection models was evaluated using the Kennard-Stone algorithm and computing the correlation between the breeding values obtained using phenotypic measurements and breeding values estimated using genomic information. Combining the NIR spectroscopy information to the genomic dataset improved the correlation coefficient estimates for FIB% and PC%. The results found in this study suggest that models including NIR spectra-derived data coupled with molecular markers information resulted in higher predictive ability. Hence, this approach could be used to enhance the efficiency of selection of sugarcane clones by reducing breeding time cycles and thus, increase genetic gains at the PMGCA.

O objetivo principal desta dissertação foi investigar novas metodologias para contornar alguns dos gargalos do programa de melhoramento genético de cana- de-açúcar da Universidade Federal de Viçosa (PMGCA). No capítulo um, desenvolvemos modelos de regressão e classificação usando espectroscopia de infravermelho próximo para prever e classificar clones de cana-de-açúcar com base em dois parâmetros de qualidade de matéria-prima. Os valores medidos por métodos de referência e previstos pelos modelos PLS e PLS-DA foram comparados. Os modelos PLS tiveram acurácias moderadas. Os coeficientes de correlação de predição obtidos foram: 0,732 para teor de fibra e 0,665 para teor de sacarose. Os modelos PLS-DA construídos para classificar clones baseados em PC% apresentaram o valor ideal de 1 para sensibilidade, enquanto os modelos baseados em FIB% apresentaram um valor moderado de 0,758. Ambos os modelos exibiram erros de classificação semelhantes: 0,185 e 0,195 para FIB% e PC%, respectivamente. Estes resultados indicam a viabilidade da espectroscopia NIR na substituição de métodos de referência adotados atualmente. No capítulo dois, investigamos se a acurácia da seleção genômica é melhorada, combinando a matriz de espectros NIR e uma matriz de SNPs em uma única análise de regressão. A acurácia dos modelos de seleção genômica foi avaliada utilizando o algoritmo de Kennard-Stone e computando a correlação entre os valores genéticos obtidos por meio de medidas fenotípicas e os valores genéticos estimados a partir da informação genômica. A combinação das informações de espectroscopia NIR e de genômica melhorou a correlação dos modelos para FIB% e PC%. Os resultados encontrados neste estudo sugerem que modelos incluindo dados derivados de espectros NIR, juntamente com informações de marcadores moleculares, resultam em maior capacidade preditiva. Assim, essa abordagem poderia ser usada para aumentar a eficiência da seleção de clones de cana-de-açúcar, reduzindo os intervalos de geração e assim possibilitar o aumento nos ganhos genéticos no PMGCA.
Keywords: Espectroscopia de infravermelho; Plantas - Melhoramento genético; Melhoramento Vegetal